INFLUENCE OF GROUPING OF THE BRIDGE PIERS ON SCOUR - Воскобійник, В. А.; Нікішов, В. І.; Воскобойник, О. А.; Воскобійник, А. В. (Science-based technologies, 2014)
Influence of grouping of the bridge piers on scour of the ground surface is investigated. Experimental research results of influence of bridge pier as three-row much pile grillage, which is placed behind of prismatic pier, on a form and depths local and global scours are presented. It is set that at the flow around single and group of bridge piers on a hard and erosion surface are generated the large-scale horseshoe vortical systems in junction region of surfaces of piers with a bottom, the intensive vortical tubes in shear layers on sides of the bluff bodies, wake vortices behind piers and jets between the close located piers. In plane axial symmetry of pier, the scour profile consists of two slopes of deposition of sand. An overhead slope has a less angle of slope and appears operating on the particles of sand of the horseshoe vortex, arising up at separation of boundary layer from the overhead frontal edge of opening of scour. The bottom slope of deposition of sand is conditioned by the action of the horseshoe vortex, which is engendered by a flow, directed to the erosion bottom along the forehand of pier. Grouping of bridge piers decreases on (10…15) % the scour depth near-by prismatic pier for subcritical velocities. For critical velocities the scour depth does not depend on grouping of piers, and for supercritical velocities the scour depth before prismatic pier increases on (15…20) %.